2018
DOI: 10.1007/s40264-018-0643-5
|View full text |Cite|
|
Sign up to set email alerts
|

Safety Communication Tools and Healthcare Professionals’ Awareness of Specific Drug Safety Issues in Europe: A Survey Study

Abstract: IntroductionNational competent authorities (NCAs) use Direct Healthcare Professional Communications (DHPCs) to communicate new drug safety issues to healthcare professionals (HCPs). More knowledge is needed about the effectiveness of DHPCs and the extent to which they raise awareness of new safety issues among HCPs.ObjectiveThe objective was to assess and compare general practitioners’ (GPs’), cardiologists’, and pharmacists’ familiarity with DHPCs as communication tools, their awareness of specific drug safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 12 publications
1
25
1
Order By: Relevance
“…Around half of the tested sample (N= 254, 58.7%) declared that they were aware of concerned safety issues, which was a comparable percentage to that found in Netherland study [11], where the awareness of most HCPs with all four safety issues ranged from (56% to 88%), while a higher percentage of (92%) was detected in the European study [14]. Generally in the current study, for the ten tested DHPCs, the sources of such information varied between HCPs where DHPC comprised (N= 149, 36.9%) compared to other sources (conferences, media, journals, colleagues, books and internet) that comprised (N= 149, 61.1%.)…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Around half of the tested sample (N= 254, 58.7%) declared that they were aware of concerned safety issues, which was a comparable percentage to that found in Netherland study [11], where the awareness of most HCPs with all four safety issues ranged from (56% to 88%), while a higher percentage of (92%) was detected in the European study [14]. Generally in the current study, for the ten tested DHPCs, the sources of such information varied between HCPs where DHPC comprised (N= 149, 36.9%) compared to other sources (conferences, media, journals, colleagues, books and internet) that comprised (N= 149, 61.1%.)…”
Section: Discussionsupporting
confidence: 54%
“…This study aimed to assess the HCPs' preferences and knowledge of DHPC and to detect barriers hindering the success of DHPC in Egypt. Three other studies were performed for a similar purpose, one in Netherland [11], another in Ghana [4] and a recent one conducted in nine European countries [14]. In the current study, HCPs of different specialties (internists, cardiologists, neurologists, pediatricians, and other specialties), with different experience years (< 20 and ≥ 20 years), several scientific degrees (Bachelor, Masters and Medical Doctorate (MD) degree), worked at different health institutions (university hospitals, educational institutes, and ministry of health) were surveyed through face-to-face interview.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] Despite this, it appears that DHPCs represent the most common source of awareness of medicines' safety issues among European GPs, pharmacists and cardiologists. [29] Previous research has indicated that such communications have greater impact on non-specialist drugs and for safety issues with a risk of death and/or disability, [8] however to date, the relationship between characteristics of DHPCs and variation in outcomes has not been evaluated. Further research should also evaluate additional interventions to communicate safety information to healthcare professionals in cluster or stepped wedge randomised controlled trials.…”
Section: Discussionmentioning
confidence: 99%